The Immunomodulatory Effects of Macrolides—A Systematic Review of the Underlying Mechanisms - Zimmermann, Petra; Ziesenitz, Victoria C.; Curtis, Nigel; Ritz, Nicole (Frontiers in Immunology, 2018)
Background: Macrolides have immunomodulatory properties. However, the mechanisms underlying the non-antimicrobial effects of macrolides are not well understood. Objectives: To systematically review the current evidence of immunomodulatory properties of macrolides in humans and to describe the underlying mechanism and extend of their influence on the innate and adaptive immune system. Methods: A systematic literature search was performed in MEDLINE using the OVID interface from 1946 to December 2016 according to the preferred reporting items for systematic reviews and meta-analysis (PRISMA). Original articles reporting the influence of four macrolides (azithromycin, clarithromycin, erythromycin, roxithromycin) on immunological markers in humans were included. Results: We identified 22 randomised, controlled trials, 16 prospective cohort studies and 8 case-control studies reporting on 47 different immunological markers (186 measurements) in 1777 patients. The most frequently reported outcomes were a decrease in the number of neutrophils, concentration of neutrophil elastase, interleukin (IL)-8, IL-6, IL-1beta, tumour necrosis factor-alpha, eosinophilic cationic protein, and matrix metalloproteinase 9. Inhibition of neutrophil function compared to eosinophils was more frequently reported. A decrease of T-helper (Th)2 cell cytokines (IL-4, IL-5, IL-6) was more frequently reported than a decrease of Th1 cytokines (IL-2, INF-gamma). Conclusion: Macrolides influence a broad range of immunological mechanisms resulting in immunomodulatory effects. To further optimise the treatment of chronic inflammatory diseases by macrolides, further studies are necessary, particularly also comparing different macrolides and dose effect relationships.